EVOLUTION OF LAW AND POLICY RELATING TO LABOUR MANAGEMENT RELATIONS - Kayala, Dr. Krishna Murty (IJRDO - Journal of Business Management, 2017)
The term ‘industrial relations’ or labour management relations’ or employee relations is difficult to define precisely because it is too complex. This is particularly so in a democratic society which allows freedom of action to the workers and their organisations and to the employers and their organisations and a series of laws are enacted to regulate their relations. In a totalitarian country trade unions are banned, as in Germany under Hitler or Italy under Moussolini. But even such a society has to enact laws to provide an acceptable relationship between the industrial employer and employees. In a Communist country where all persons employed are workers, industrial relations cannot result in any form of industrial action. But changes are taking place even in the so-called Communist countries; the upsurge of industrial workers in Poland and Yugoslavia are cases to point.